Density functional theory calculations of structure-antioxidant activity of selected phenolic acids and flavonoids found in Malaysian honey - Rosmahaida Jamaludin,; Nurazean Maarop,; Siti Fatimah Zaharah Mustafa,; Hasmerya Maarof,; Usman, Bishir (Penerbit Universiti Kebangsaan Malaysia, 2019)
Phenolic acids and flavonoids exist naturally in Malaysian honey and contribute significantly to antioxidant contents. Antioxidants plays an important role in scavenging free radicals and prevent health deterioration. Total antioxidant content is measured using DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity. The phenolic acids such as gallic, caffeic, syringic and hydroxybenzoic acids and flavonoids like naringenin, apigenin, kaempferol, catechin and luteolin previously have been identified in Malaysian honey of tualang, gelam and borneo type using high-performance liquid chromatography (HPLC). In order to investigate the structure-antioxidant activity relationships of these phenolic compounds using hydrogen atom transfer (HAT) mechanism, density functional theory (DFT) calculation at B3LYP/6-311++G(d,p) levels of theory was performed. In this work, optimization of the compounds chemical structure and radical forms in gas-phase has been calculated with computation of bond dissociation enthalpy (BDE) as antioxidant descriptor. The finding showed that abstraction of H at different OH groups in the structure of the compound, led to a different scavenging free radical activity thus contribute to the overall variation in the antioxidant properties. Besides that, B ring of flavonoids and unsaturated bond in pyran ring are proposed factors that could lower the BDE values and consequently influence the antioxidant properties of the antioxidant compounds. Hence, DFT calculation with BDE descriptor had been successfully applied to investigate the relationship between structure of phenolic acids and antioxidant activity of Malaysian honey and the interesting results could contribute in future development of antioxidant compound.